Evaporative Cooling Window System With Labu Sayong For Reducing Indoor Temperature In Hot-Humid Tropics - Ahmad, Nur Hidayah (2017)
In reducing indoor temperatures, an evaporative cooling window system (ECWS) using labu sayong integrated with mechanical ventilation and energy operated using solar electricity is one of the most preferable strategies to be applied in hot-humid tropic countries like Malaysia. This system will help tackle the issue of increasing costs in keeping the home cool by managing energy consumption and also offers a better indoor environment.